2007
DOI: 10.1021/ja068950t
|View full text |Cite
|
Sign up to set email alerts
|

A Room Temperature Negishi Cross-Coupling Approach to C-Alkyl Glycosides

Abstract: C-Glycosides represent an important class of bioactive compounds that are resistant to metabolic processing. 1,2 Although crosscoupling reactions are obvious approaches to these compounds, the sensitivity of C1-substituted organometallics to β-elimination processes (hydride or alkoxy) is the generally accepted reason why fully oxygenated and saturated structures are not typically accessible via these methods. [3][4][5] This notion is generally true of the synthetic methods that generate nucleophilic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(72 citation statements)
references
References 9 publications
1
67
0
4
Order By: Relevance
“…Gagné and coworkers reported another example of a Ni-catalyzed Negishi coupling between functionalized alkylzinc reagents and secondary glycosidic halides 205. It was observed that NiCl 2 with an achiral Pybox ligand lead to good product yields, and mannosyl halides were diastereoselective for retentive C1 -alkylation.…”
Section: Alkylzinc Reagentsmentioning
confidence: 99%
“…Gagné and coworkers reported another example of a Ni-catalyzed Negishi coupling between functionalized alkylzinc reagents and secondary glycosidic halides 205. It was observed that NiCl 2 with an achiral Pybox ligand lead to good product yields, and mannosyl halides were diastereoselective for retentive C1 -alkylation.…”
Section: Alkylzinc Reagentsmentioning
confidence: 99%
“…_ 7 ) T D $ F I G ] Halogenated anomeric sugars can also be substituted with zinc derivatives in the presence of nickel complexes in an aprotic polar solvent (Negishi cross-coupling). This reaction selectively gives the a-C-glycosides in moderate to good yields (Table 2) and reflects nickel insertion into the carbon-halogen bond with retention of configuration [83,84].…”
Section: Coupling Between An Electrophilic Anomeric Carbon and A Nuclmentioning
confidence: 90%
“…[42] Gagné and co-workers reported the coupling of glycosyl halides with alkyl-and arylzinc reagents by using NiCl 2 -Pybox (44, R = H) as the catalyst. [43] Lin et al suggested a Ni I -Ni III mechanism for the reaction of racemic secondary alkyl electrophiles on the basis of a DFT calculation study. [44] In 2007 Cárdenas et al reported a Ni(py) 4 Cl 2 -(S)-sBuPybox-catalyzed cascade formation of C(sp 3 )-C(sp 3 ) bonds by cyclization and cross-coupling of alkylzinc reagents with alkyl iodides containing an alkene group (Table 10).…”
Section: Negishi Reactionsmentioning
confidence: 99%